Social capital, community based management, and fishers’ livelihood in Bangladesh - Islam, Ghazi Md. Nurul; Tai, Shzee Yew; Abdullah, Nik Mustapha R.; Viswanathan, K. Kuperan (Elsevier, 2011)
This paper examines the impact of Community Based Fisheries Management (CBFM) on fishing households’ welfare in Bangladesh. It analyses how the various types of livelihood assets contribute to fishers’ household incomes. The study found that fishers in CBFM project areas have improved their access to different assets including social, human, physical, financial and natural capitals. The regression results show that social capital contributed significantly to household income, indicating that social factors play very important roles in poverty alleviation in Bangladesh. Future poverty alleviation policy options need to give priority to investments in human, physical and natural capital assets.